One-Pot Highly Regioselective Synthesis of Indole-Fused Pyridazino[4,5-b][1,4]benzoxazepin-4(3H)-ones by a Smiles Rearrangement - Jiang, Xiaolei; Hu, Fangdong (Synlett, 2018)
A simple and convenient synthesis of indole-fused pyridazino[4,5-b][1,4]benzoxazepin-4(3H)-ones is described. A range of 2-(1H-indol-2-yl)phenols and 4,5-dichloropyridazin-3-ones are compatible with this reaction. A Smiles rearrangement is proposed as a key step in the highly regioselective construction of the products. The easy availability of the starting materials makes this an appealing method in organic synthesis.
Keywords: indoles; indolopyridazinobenzoxazepinones; regioselectivity; polycyclic heterocycles; Smiles rearrangement